Color Doppler Imaging of the Orbital Vessels in Ankylosing Spondylitis. (2nd November 2015) - Ozsahin, Mustafa; Buyukkaya, Ramazan; Besir, Fahri Halit; Onder, Halil Ibrahim; Erdogmus, Besir; Ataoglu, Safinaz; Güclü, Derya; Kolukisa, Rumeysa
Abstract: Purpose : To analyze the hemodynamic features of orbital blood flow velocities using Doppler ultrasonography in ankylosing spondiylitis (AS) patients, as well as to compare these results with those of healthy controls. Methods : 33 AS patients and 32 healthy controls were consecutively included in the study groups. The same radiologist performed ocular blood flow measurements. Peak systolic velocity (PSV), end diastolic velocity (EDV), and resistive index (RI) were measured in the central retinal artery (CRA), posterior ciliary arteries (PCAs), and ophthalmic artery (OA). Resistive index was used to assess arterial resistance; it was automatically calculated as RI [(PSV–EDV)/PSV]. Results : There were no significant differences in the PSV, EDV, and RI of the OA, CRA, and PCAs between AS patients and controls. Conclusion : This result suggests no possible contributory role of vascular structures in formation of uveitis in AS. We believe that our preliminary results need to be complemented with further studies, particularly including AS patients with uveitis and rheumatic diseases with other ocular involvement.